Evaluation of microstructure high chrome austenitic stainless-steel grade 253MA after creep test at temperature of 700°C - Alviana, Rifda Muthia; Anwar, M Syaiful; Siradj, Eddy S (Jurnal Pendidikan Teknologi Kejuruan, 2023)
High Chrome Austenitic Stainless-Steel grade 253 MA is a material that widely used for high temperature. This is due the fact this material has excellent mechanical properties and creep resistance. However, changes in microstructure can occur in long-term use, which will affect the creep resistance (shortened service life of the material). The microstructure of High Chrome Austenitic Stainless-Steel 253 MA creep test specimens was investigated. Creep testing at a temperature of 700 °C with a loading of 150 MPa was carried out. The cold rolling process with 53% reduction in thickness was applied followed by annealing at 900°C, 1000°C, and 1100°C for 3600s to obtain different grain size. Grain size after annealing and after creep test was measured to see the effect of annealing temperature on the grain size of tested steel and to see its effect on creep resistance based on the creep test conducted. Grain size and morphology of the phase after creep test were observed by scanning electron microscope and optical microscope